TEACH SCIENCE MAKING SCIENCE: AN EXPERIENCE IN BASIC EDUCATION OF BRAZILIAN SEMIARID - Ferraz, Ferraz; Lima, Diorminda de (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The purpose of this research is to evaluate the methodology of scientific research - Teaching science by making science -in the practical context, with a view to construction of educational paradigms in basic education. This is a case study carried out initially in vacations courses sponsored by the Espa§oCiªncia with teachers and managers of the municipal school system, and bachelor’s degree students in Biological Sciences from the Centro de Ensino Superior do Vale do S£o Francisco and later with 25 tutors who taught their classes using this methodology in elementary and high school education. The results of this research demonstrate approval of the methodology by 76% of managers, 57% of teachers, and 100% of students in the course of Biological Sciences who participated in the vacation courses. They have tutors who have used this methodology in elementary school and high school approved with percentage corresponding to 100% and50.70% respectively. Regarding the methodology investigated the following categories were evaluated: student participation, learning, quantity and quality of content, skills and mobilized skills by students of basic education, as well as the perception of worshipers as the advantages and disadvantages in the application of the methodology for their levels of education.